Cooperative OFDM based Maximum-Ratio Transmission - Gucer, Ozgur; Birol, Asli; Gucluoglu, Tansal (IEEE, 2015)
In this paper, a system employing orthogonal frequency division multiplexing based maximum-ratio transmission technique is presented for cooperative communications. Since maximum ratio transmission can achieve full diversity when used at tranmitters having multiple antennas while requiring no complexity increase at the receiver, it is employed both in the transmitter and in the relays of the cooperative case. The performance of the systems are studied over Rayleigh fading channels for cooperative and non-cooperative cases and simulation results of the scenarios of varying number of transmitter antennas and relays are presented.
Keywords: maximum ratio transmission; cooperative communication; amplify-and-forward relaying; orthogonal frequency division multiplexing; Engineering; Telecommunications